Report of two cases of recurrent scalp dermatofibrosarcoma protuberans and literature review - Long Liansheng; Li Xialiang; Zhao Yaodong; Xue Yajun; Lou Meiqing (Wolters Kluwer Medknow Publications, 2014)
Dermatofibrosarcoma protuberans (DFSP) are rare malignant skin tumor, and scalp DFSP is even lesser than 5% of all DFSP, therefore, being seldom reported. We recently treated two cases of recurrent scalp DFSPs. One was a 38-year-old male, who accept lumpectomy for the first time; however, it recurred 9 months later. We then performed a wide excision resulting in no recurrence in the subsequent 4 years. Another patient was a 26-year-old female, who accept an in situ tumorectomy for the first time, and 2 years later; the recurrent mass became 9 × 9 cm in size. We gave her another operation, but only 3 months later local recurrence appeared. For the both cases, we collected their case histories, intraoperative findings, pathologic detections, and follow-up results, all of which may help the dermatologists to extend knowledge about this rare disease. Moreover, an exhaustive review of the literature is included with emphasis on diagnosis, different diagnosis and treatments.